Role of mitochondria-bound HK2 in rheumatoid arthritis fibroblast-like synoviocytes - Torres, Alyssa; Kang, Sarah; Mahony, Christopher B.; Cedeño, Martha; Oliveira, Patricia G.; Fernandez-Bustamante, Marta; Kemble, Samuel; Laragione, Teresina; Gulko, Percio S.; Croft, Adam P.; Sanchez-Lopez, Elsa; Miyamoto, Shigeki; et al. (Frontiers in Immunology, 2023)
Background: Glucose metabolism and specifically HK2 has a critical role in RA FLS phenotype. HK2 localizes not only in the cytosol but also in the mitochondria where protects mitochondria against stress. We hypothesize that mitochondrial-bound HK2 is a key regulator of RA FLS phenotype. Methods: HK2 localization was evaluated by confocal microscopy after FLS stimulation. RA FLS were infected with GFP, full-length (FL)-HK2 or HK2 lacking its mitochondrial binding motif (HK2ΔN) expressing adenovirus (ad). RA FLS were also incubated with methyl jasmonate (MJ, 2.5mM), tofacitinib (1uM) or methotrexate (1uM). RA FLS were tested for migration and invasion and gene expression. Gene associations with HK2 expression were identified by examining scRNA-seq data from murine models of arthritis. Mice were injected with K/BxN serum and given MJ. ad-FLHK2 or ad- HK2ΔN were injected into the knee of wild-type mice. Results: Cobalt chloride (CoCl2) and platelet-derived growth factor (PDGF) stimulation induced HK2 mitochondrial translocation. Overexpression of the HK2 mutant and MJ incubation reversed the invasive and migrative phenotype induced by full-length HK2 after PDGF stimulation, MJ also decreased expression of CXCL1 and COL1A1. Of interest, tofacitinib but not methotrexate had an effect on HK2 dissociation from the mitochondria. In murine models, MJ treatment significantly decreased arthritis severity, while HK2FL was able to induce synovial hypertrophy as opposed to HK2ΔN. Conclusion: Our results suggest that mitochondrial HK2 regulates the aggressive phenotype of RA FLS. New therapeutic approaches to dissociate HK2 from mitochondria offers a safer approach than global glycolysis inhibition.